Pengaruh Pembelajaran Fisika Menggunakan Model SETS (Science, Environment, Technology, and Society) Terintegrasi Mitigasi Bencana Alam Terhadap Kemampuan Analisis dan Transferable Skills Peserta Didik - Fitri Yayu Indrawati; Siska Desy Fatmaryanti; Arif Maftukhin (Universitas Muhammadiyah Purworejo, 2019)
This research aims to know (1) the influence of SETS Learning model integrated natural disaster mitigation for the analytical ability and scientific communication ability of students, (2) Student activities when applied SETS learning models. This research uses the Quasi-experiment method. Research conducted at SMK Computer Karanganyar with the subject of research is 18 students class X Akutansi and 30 X Multimedia classes. The instruments used in this research are the analytical skills sheet, analysis of scientific communicational ability sheet, and earthquake mitigation poll in this study, including validation test, reusability test, normality test, homogeneity test, N-Gain test, hypothesis test. Based on test data analysis results, there is a result that there is an influence of the model learning SETS integrated mitigate natural disasters on the analytical skills and scientific communication skills of learners. This is based on the results of the N-gain test with increased analytic ability in the experimental class of 0.31 with a medium category, and the control class with a gain value of 0.25 with a low category. While the enhancement of experimental class scientific communication capabilities was 0.36, and the control class was 0.24. Based on the hypothesis test results using the test paired Sample T-Test There is a comparison of learning skills analysis and the ability of scientific communication in experimental classes and the control class is good. In addition, learning physics using SETS learning models also provide increased student activity in experimental classes.